Molecular Electronic Structures of Transition Metal Complexes II - Mingos, David Michael P.; Day, Peter; Dahl, Jens Peder (Structure and Bonding, 2012)
T. Ziegler: A Chronicle About the Development of Electronic Structure Theories for Transition Metal Complexes.- J. Linderberg: Orbital Models and Electronic Structure Theory.- J.S. and J.E. Avery: Sturmians and Generalized Sturmians in Quantum Theory.- B.T Sutcliffe: Chemistry as a "Manifestation of Quantum Phenomena" and the Born-Oppenheimer Approximation?- A.J. McCaffery: From Ligand Field Theory to Molecular Collision Dynamics: A Common Thread of Angular Momentum.- M. Atanasov, D. Ganyushin, K. Sivalingam and F. Neese: A Modern First-Principles View on Ligand Field Theory Through the Eyes of Correlated Multireference Wavefunctions.- R.S. Berry and B.M. Smirnov: The Phase Rule: Beyond Myopia to Understanding.